Medical clerkship rotation in government hospitals student perceptions on the learning experience - Chiongson, Desiree E.; Nemuel S. Fajutagana MD MHPEd (2005)
In Philippine medical schools, the second month of rotation in a major field or specialty is usually spent on outside rotation in government hospitals to provide the students with a wider field of experience and a larger variety of patient which they don't see in their schools' teaching hospital. This study describes what clerkship rotations in government hospitals are like based on interviews with training officers of the involved hospitals and review of written documents pertaining to their clerkship training programs. It also describes the medical students' perceptions and reflections on their learning experience in these institutions based on responses to 2 sets of questionnaires: 1) a survey where students choose on a 5-point scale their level of agreement or disagreement to positively stated statements regarding the learning experience based on the experiential learning cycle, and 2) a reflection questionnaire which was based on the components of the clerkship program described by the training officers of the hospitals. Results of the survey revealed that the students' perceived learning experience vary according to the hospital rotations. Hospitals that provided more hands-on experiences and therefore entailed greater student involvement were perceived to be more satisfactory than hospitals where the clerks are confined to being observers and doing routine ward works. The following factors were also found to have contributed to the clerks' dissatisfaction during their rotation: 1) lack of guidance, 2) poor esteem needs support, 3) poor knowledge base acquisition, 4) unavailability of feedback, no opportunity for reflection, 5) lack of opportunity to process learning In conclusion, except in the hospital where clerks were confined to monitoring and observing, clerks has a favorable overall impression of their rotations despite their misgivings. This is attributed to the opportunity to see more number and variety of cases in the government hospitals that they would otherwise not see in their base hospitals, the opportunity to perform some procedures, and the social awareness brought about by the rotation. Furthermore, the clerks have gone through several outside rotation at the time of this study and have been through similar working conditions that the circumstances surrounding their rotations in the involved hospitals are not new to them. A further possibility is the common notion among medical students that all the hardships are part of the process of becoming doctors.
Thesis (Master in Health Professions Education)--University of the Philipines Manila
Panel Members: Nemuel S. Fajutagana MD MHPEd, Chair/Adviser; Erlyn A. Sana PhD, Reader/Critic; Jose Alvin P. Mojica MD MHPEd, Member; Cristina F. Mencias MHPEd PhD, Member; Lupe F. Abarquez BSN MHPEd, Member.
Keywords: Medical clerkship